Industry-specific strategies in a protectionist world - Robert Ballance (Intereconomics, 1985)
The period from 1950 to 1974 was one of exceptional economic progress, particularly in manufacturing. This article examines how some of these developments have altered the objectives and methods of formulating industrial policy in western countries. Following a brief discussion of sector-wide policies and strategies, evidence from two industries—steel and advanced electronics—is used to illustrate the growing range of strategic choices and the interaction between public policy-makers and private industry. Finally, some generalizations with regard to industry-specific strategies are presented.
Keywords: 330; Industrial Policy